Diagnostic and prognostic utility of the platelet parameters in patients with acute myocardial infarction - D. V. Zhehestovska; M. V. Hrebenyk (Kazimierz Wielki University, 2021)
Background. Complete blood count (CBC) is a simple and affordable diagnostic tool that is routinely used in therapeutic practice. At the same time, its diagnostic and prognostic potentials in terms of management of acute myocardial infarction (AMI) are currently limited. Based on a number of previous studies, we suggest that the analysis of platelet count and indices among AMI patients may have significant diagnostic and prognostic value, as well as dynamic changes in these parameters during the treatment course. Objectives. To evaluate the value of platelet indices and ratios in terms of their diagnostic and prognostic potential among patients with AMI at the time of hospitalization and on the 7th day of treatment. Materials and methods. The study involved 152 patients diagnosed with AMI (Group 1), 30 patients diagnosed with the chronic coronary syndrome (Group 2) and 24 healthy volunteers (Group 3). CBC was performed for all participants to determine all platelet indices. Also, anamnestic and clinical data were evaluated, as well as results of the coronary angiography. GRACE score was calculated. Results. The highest diagnostic value was shown by the WBC/MPV ratio (AUC 0,798; sensitivity 83,1 %; specificity 65,1 %) and PLT/L ratio (AUC 0,644; sensitivity 62,7 %; specificity 53,5 %), as opposed to traditionally used MPV (AUC 0,426; sensitivity 47,5 %; specificity 48,8 %) and PLT (AUC 0,484; sensitivity 60,8 %; specificity 58,1 %). We were unable to establish a relationship between CBC platelet counts at the time of hospitalization and the risk of complications according to the GRACE score. However, those changes according to CBC were obtained on the 7th day of treatment. In particular, the number of platelets was associated with the risk of hospital (r = 0,287; p = 0,016) and 6-month mortality (r = 0,260; p = 0,30), the duration of ischemia (r = 0,238; p = 0,016) and the number of affected vessels according to the results of angiography (r = 0,395; p = 0,002). Similarly, P-LCC correlated with the risk of hospital (r = 0,483; p = <0,001) and 6-month mortality (r = 0,462; p = <0,001), the number of affected coronary vessels (r = 0,456; p = 0,001) and the duration of angina pectoris (0,392; p = 0,001), respectively. Conclusion. We found that combined ratios such as WBC/MPV and PLT/L had a higher diagnostic value compared to MPV, PLT and P-LCR. The prognostic potential of platelet indices was significantly higher on the 7th day of hospital stay. In particular, elevated levels of platelets, platelets, and P-LCR were correlated with a higher risk of hospital and 6-month mortality.